Pengujian Jaringan Saraf Tiruan Dalam Mendiagnosa Gangguan Jiwa Menggunakan Algoritma Backpropogation Levenberg-Marquardt - Solikhun Solikhun; Sundari Putri Lestari (Journal of Information System Research (JOSH), 2023)
Mental disorders are mental health issues that make it hard to meet one's own or other people's needs. A person's life may be affected by changes in behavior brought on by this condition. To conquer this issue, a backpropagation calculation has been created to help with distinguishing mental problems. This calculation utilizes information got from mental tests to distinguish early indications of mental problems in an individual. With this calculation, psychological wellness experts can settle on additional quick and precise symptomatic choices. The Levenberg-Marquadt method and the backpropogation algorithm were used in this study to diagnose mental disorders. The aim of this study is to make it easier to diagnose mental disorders by analyzing a patient using the 24 attributes of the questions. After the diagnosis is made, the results will show up, and the Levenberg-Marquardt Backpropagation Algorithm will be used to test a person to see if they have bipolar disorder, OCD, or any other disorder. Researchers will have a difficult time determining the patient's mental illness if this diagnosis is not carried out. The aftereffects of this study are as demonstrative inquiries for mental issues that have been given. The Levenberg Marquadt method backpropagation algorithm is the bridge to accuracy, supporting this study's success. MSE is 24-10-1, with training performance equal to 0.000014246 and testing performance equal to 0.0000146. The diagnosis that comes out of it is more accurate the less error there is.